Implementation of the IDUKA-based curriculum in forming outstanding students at SMK Muhammadiyah 7 Gondanglegi - Yunus, Muhammad (Maliki Interdisciplinary Journal, 2024)
The Indonesian government has launched a curriculum synchronization program with the World of Industry and the World of Work (IDUKA) to ensure that Vocational High School (SMK) graduates have competencies relevant to the world of industry and work. The method the author used for this research was the descriptive qualitative method. The curriculum management at SMK Muhammadiyah 7 Gondanglegi is structured in Dual System Education (PSG), with 60-70% of the application in practice and 30-40% in theory. The curriculum is synchronized with industry needs, including classrooms, practice rooms, tools, materials, and industry culture. IDUKA's role as a center for vocational schools is crucial in producing a generation that is qualified and able to compete in the world of work, following existing technological developments.